Features of the realization of the teaching of the category of politeness - Diana Maratova Zinnurova, Svetlana Yurievna Glushkova, (Opción, 2019)
In this article, an attempt is made to identify the specifics of the functioning of the category of politeness in Chinese and its linguistic means via semantic-stylistic and comparative methods. As a result, in Chinese the use of certain polite words in speech depends on the specific situation, the context of communication and the social status of communicants. In conclusion, studying of any foreign language as a means of communication should go in hand with learning the cultural aspects of the country and its people.